STRATEGI PENGADAAN CALON PEGAWAI NEGERI SIPIL YANG BERKUALITAS1 - Janry Haposan U.P Simanungkalit (Jurnal Manajemen Kepegawaian, 2008)
One of civil service reform urgent agenda in Indonesia for shortly been done is reform of civil servant candidates (CPNS) procurement, remembering that it is the most deep critical thing in the entirely of civil service management process. This study result shows that generically, civil servant candidates procurement that held by Government Institution on exhaustive locus study went on good and smooth, even it still has not yet fully free of deviation practices (KKN). Base on strategy analysis result by using SWOT Analysis, this study recommend strategy formulation for qualified civil servant candidates procurement in the future, namely: (1) speeding up reform actualise and enhancing transparency and accountability of the civil servant candidates procurement on all steps; (2) establishing civil service job competency standard nationally; (3) improving civil service planning system comprehensivelly; (4) upholding law and sanction implementing for each KKN’s actions in the civil servant candidates procurement processes; (5) realizing competitive and equity (internal and external) civil service remuneration system; and (6) advance merit’s principles in the civil I